2023
DOI: 10.1007/s11883-023-01090-6
|View full text |Cite
|
Sign up to set email alerts
|

How Can Implementation Science Improve the Care of Familial Hypercholesterolaemia?

Abstract: Purpose of Review Describe the application of implementation science to improve the detection and management of familial hypercholesterolaemia. Recent Findings Gaps between evidence and practice, such as underutilization of genetic testing, family cascade testing, failure to achieve LDL-cholesterol goals and low levels of knowledge and awareness, have been identified through clinical registry analyses and clinician surveys. Implementation science theories,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…By interviewing patients and providers, we are addressing this important element by understanding, from the perspective of the end user, why the primary-tertiary shared care model may or may not be successful. Despite the strong evidence base behind FH care, efforts to translate guidelines into practice are often unsuccessful, likely related to a lack of relevant or appropriate implementation strategies 17 31. The design of this study protocol has taken into consideration previously identified barriers and enablers by this research group allowing for the selection of appropriate implementation strategies tailored to local needs 13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By interviewing patients and providers, we are addressing this important element by understanding, from the perspective of the end user, why the primary-tertiary shared care model may or may not be successful. Despite the strong evidence base behind FH care, efforts to translate guidelines into practice are often unsuccessful, likely related to a lack of relevant or appropriate implementation strategies 17 31. The design of this study protocol has taken into consideration previously identified barriers and enablers by this research group allowing for the selection of appropriate implementation strategies tailored to local needs 13.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to develop implementation strategies to effectively create and operationalise new models of care for the translation of FH clinical practice guidelines into practical application 17. Furthermore, models of care should be adaptable to suit local needs and be acceptable to patient and provider 5 18.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting implementation science frameworks and practices may also facilitate the uptake of guideline-directed genetic testing. Proposed implementation science strategies include leadership engagement, attention to the structure and clarity of guidelines, and the creation of clinical resources to support implementation of recommendations ( 54 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, several drivers of this ‘know-do’ gap have been identified and can inform efforts to promote cascade screening. These include costs and insurance coverage for screening; probands or relatives having concerns related to privacy and discrimination, limited knowledge of FH, or low health literacy; challenging family relationships; clinicians lacking awareness or perceiving FH as low urgency; competing demands on clinicians’ time; and challenges with collaboration among clinicians [ 43 , 44 ].…”
Section: Research-to-practice Gapmentioning
confidence: 99%